When Bleeding Stops but Organs Fail: Fatal Multiple Organ Dysfunction Syndrome Following Massive Atonic Postpartum Haemorrhage in a Young Primipara — A Case Report - Rina Gustuti; Arianti Arifin; Yusrawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Postpartum haemorrhage from uterine atony can precipitate profound haemorrhagic shock within minutes, and in resource-constrained referral systems the interval between the onset of bleeding and definitive source control is frequently the decisive determinant of survival. Case presentation: We describe a 28-year-old primipara referred four hours after a vacuum-assisted vaginal delivery of twins complicated by severe pre-eclampsia. On arrival she was stuporous, hypotensive (70/68 mmHg), tachycardic (142 beats/min) and oliguric, with active vaginal bleeding and a haemoglobin of 2.4 g/dL. Resuscitation and haemorrhage control proceeded in parallel: high-flow oxygen, dual large-bore access, crystalloid and colloid loading, tranexamic acid, balanced blood-component transfusion, bimanual compression, intubation and emergency laparotomy. A flaccid, bluish, atonic uterus and a fourth-degree perineal tear were identified; subtotal hysterectomy with sphincteroplasty and perineorrhaphy achieved haemostasis. Despite massive transfusion and intensive care, prolonged hypoperfusion evolved into ischaemic hepatitis, severe coagulopathy, stage III acute kidney injury requiring haemodialysis, hospital-acquired pneumonia with drug-resistant sepsis, acute pulmonary oedema and upper gastrointestinal bleeding. Progressive multiple organ dysfunction syndrome culminated in asystolic cardiac arrest on postoperative day 15. Conclusion: This case illustrates a principle easily overlooked: definitive surgical haemostasis does not reverse organ injury already committed during the pre-operative shock interval. Objective cumulative blood-loss measurement, immediate haemorrhage-bundle and massive-transfusion protocol activation, explicitly documented uterotonic therapy, rapid balanced resuscitation and structured post-haemostasis organ surveillance are the interventions most likely to interrupt the lethal trajectory.